(untitled) (Bangladesh Journal of Zoology, 2017)
Diversity of ichthyofauna of Feni and Muhuri rivers was studied from April, 2015 to March 2016. The selected rivers were surveyed to cover the wet season (April 2015-September 2015) and the dry season (October 2015-March 2016). A total of 65 freshwater fish species belonging to 11 orders, 29 families were recorded from the two rivers. Of the 65 species, 12 species were threatened, and one species was identified as data deficient according to IUCN Bangladesh. Perciformes was recorded as most dominating order (19 species, among the 54 species recorded) in Feni river, whereas the Cypriniformes was recorded as the dominating order (17 species among the 42 species recorded from this river) in Muhuri river. Corica soborna was the most common species with the highest number of individuals in comparison to other fish species recorded from two rivers in both wet and dry seasons. Calculating the Shannon-Weiner and Simpsons indices of diversity and species evenness, highest number of species and individuals were found in the wet season while minimum in the dry season from both the rivers. Bangladesh J. Zool. 45(1): 47-60, 2017